Sapphirine as a breakdown product of garnet in a Variscan UHP/HT peridotite from the Vosges Mountains (France): an indication of near-isothermal decompression - Altherr, Rainer; Soder, Christian (Journal of petrology, 2018)
Abstract. In the Variscan Vosges Mountains (France) small bodies of orogenic garnet peridotite occur within felsic gneisses (former granulites). In most of these peridotite bodies the original garnet is completely transformed to kelyphite surrounded by a relatively thin two-layer corona of orthopyroxene ± clinopyroxene and orthopyroxene + clinopyroxene + spinel, which was formed during decompression and reflects the transition from garnet peridotite to spinel peridotite. The porphyroblastic garnet peridotite of Laveline-du-Houx originally formed at 4·1± 0·2 GPa and 1000 ± 20°C, as shown by geothermobarometry on relics of pyroxene and garnet. Geochemically, the rock is only moderately depleted relative to primitive mantle. It contains mineralogically zoned pseudomorphs after garnet, which formed during exhumation and allow for reconstruction of the retrograde pressure-temperature (P–T) path. Inside the commonly present, marginal, two-layer corona of these pseudomorphs, there follow two additional spherical shells: a relatively thick shell consisting of Al-rich pyroxenes (with small inclusions of chemically modified garnet relics) and spinel followed by an inner shell containing the assemblage sapphirine + Al-rich orthopyroxene + Al-rich clinopyroxene ± spinel. Both shells were generated by metasomatic reactions (introduction of Na and Ca) between garnet and olivine at pressures between about 2·3 and 1·0 GPa and temperatures of 950–1000°C. Increasing infiltration of water during exhumation is documented by inclusions of aspidolite in spinel and by formation of amphibole in the sapphirine-bearing zone. Locally, spaces between Al-rich orthopyroxene and clinopyroxene reacted to olivine, plagioclase and minor amounts of Al-poor pyroxenes, indicating pressures below ∼0·7 GPa. Moreover, sapphirine became partially or completely converted to fine-grained symplectitic aggregates of spinel and plagioclase, and Al-rich clinopyroxene partially reacted to a very fine-grained symplectite of amphibole, plagioclase, and minor spinel. Relic garnet in the central parts of the pseudomorphs was almost completely transformed to kelyphite. The near-isothermal exhumation path of this small ultramafic body indicates rapid exhumation that seems only possible within a larger mass of less dense, more felsic rocks, which also underwent ultrahigh-pressure metamorphism, but reequilibrated much faster and more efficiently than its ultramafic passenger during uplift.